2010
DOI: 10.1111/j.1365-2958.2010.07277.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological and structural characterization of the Mycobacterium smegmatis nitroreductase NfnB, and its role in benzothiazinone resistance

Abstract: SummaryTuberculosis is still a leading cause of death in developing countries, for which there is an urgent need for new pharmacological agents. The synthesis of the novel antimycobacterial drug class of benzothiazinones (BTZs) and the identification of their cellular target as DprE1 (Rv3790), a component of the decaprenylphosphoryl-b-D-ribose 2Ј-epimerase complex, have been reported recently. Here, we describe the identification and characterization of a novel resistance mechanism to BTZ in Mycobacterium smeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
121
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 74 publications
(124 citation statements)
references
References 41 publications
3
121
0
Order By: Relevance
“…Our group also identified and characterized a novel resistance mechanism to benzothiazinones in M. smegmatis (Manina et al, 2010a), and this mechanism was confirmed also for dinitrobenzamides (M.R. Pasca, personal communication).…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…Our group also identified and characterized a novel resistance mechanism to benzothiazinones in M. smegmatis (Manina et al, 2010a), and this mechanism was confirmed also for dinitrobenzamides (M.R. Pasca, personal communication).…”
Section: Introductionmentioning
confidence: 57%
“…In this context, another novel resistance mechanism to BTZs was described in M. smegmatis (Manina et al, 2010a). The over-expression of the nitroreductase NfnB leads to the inactivation of the drug by reduction of a critical nitro group to an amino group (Figure 3).…”
Section: Benzothiazinonesmentioning
confidence: 96%
See 3 more Smart Citations